Сурах бичгийн чанарыг сайжруулах шаардлага, арга зүйн боломжууд - Д., Цэвээндорж (Mongolian Studies, 2023)
In this article suggested that some new idea to improve textbooks quality of Mongolian educational system. For example, training team (teacher’s book - textbook - pupil’s book) or comprehensive teaching aid and wall charts because of discovered some grammar and other mistakes by content, instructional properties, technology integration, teachers guide, assessment properties and other genres. In vocabulary, to choose an appropriate word a child’s age and psychology, use an official terms and terminology and avoid foreign words by certain writing skills in textbooks of high schools. Technical editors should choose from the linguistics, and general editors should be specilized and skillful writers. When editing many times that textbooks becoming more difficult to the learners. According to authors should be deep knowledge and an innovative with foreign languages. Also, to introduce a new teaching method and should know an ISD, Kemp models, Bloom’s taxanomy and other international methods or evaluation criteria for textbooks.